The Impact of an Audience on the Appeal of Virtual Reality - Woods, Andy T.; Whittaker, Laryssa; Verhulst, Isabelle; Bennett, James; Dalton, Polly (Frontiers in Virtual Reality, 2022)
Virtual reality in a public place is enticing for some yet daunting for others. Social Impact theory proposes that performing in front of larger (vs. smaller) audiences is typically seen as more anxiety provoking and less desirable. Having peers perform with you can offset this, however. Our goal was to test whether Social Impact theory extends to the context of trying virtual reality in a busy public setting, and whether any such effects are influenced by extraversion and trait anxiety. In Experiment 1, we ran an online study with 100 participants and found that images of people trying virtual reality in front of others were indeed rated as more anxiety provoking than images with no audiences. Images with (vs. without) audiences were also rated as scenarios in which people would be less willing to try virtual reality. There was no impact of extroversion levels on people’s reported Willingness to Try; however extroverted individuals were less affected by audience size compared to introverts in terms of how anxiety-provoking they considered the scenario. Experiment 1 also found that the presence of a monitor showing one’s virtual reality ‘performance’ made Extroverts keener to try the experience, yet Introverts less keen. Experiment 2 tested whether the main findings of the first study extended to a real-world scenario. 69 participants observed 0-3 individuals trying a virtual-reality experience in the foyer of a busy library and were then questioned on expected anxiety levels and Willingness to Try. Whilst anxiety levels were again influenced by the audience size (number of people in the foyer at the start of each test), there was no impact of audience size on Willingness to Try virtual reality. Note that relative inattention of the audience on those trying VR in Experiment 2 (compared to Experiment 1), as well as a small sample size, may have made it hard to detect effects here. Extroverts were again less anxious about trying VR in-front of others compared to introverts. These findings offer some ways to make public space virtual reality experiences more accessible, whilst suggesting future steps to properly assess some exploratory findings presented here.